Study on the influence of 7-β-hydroxy-γ-aryloxypropylxanthinyl- 8-thioalkanic acid derivatives on the lipid metabolism in experiment - Bilai, I. M.; Romanenko, M. I.; Ivanchenko, D. H.; Білай, Іван Михайлович; Романенко, Микола Іванович; Іванченко, Дмитро Григорович; Белай, И. М.; Романенко, Н. И.; Иванченко, Д. Г. (Запорізький державний медичний університет, 2021)
noted. All of this determines scientists to find new effective and low-toxic hypolipidemic agents. Various natural and synthetic xanthine derivatives have been recognized as therapeutically potential compounds and reported to control various diseases. Therefore, the study of new xanthine derivatives and their hypolipidemic effects, which would have a significant therapeutic effect with minimal side effects, is relevant. The aim of the study was to examine the effect of 7-β-hydroxy-γ-aryloxypropylxanthinyl-8-thioalkanic acid derivatives on lipidogram parameters in experimental laboratory rats. Materials and methods. The objects of the study were 7-β-hydroxy-γ-aryloxypropylxanthinyl-8-thioalkanic acid derivatives. The experiments were performed in white laboratory Wistar rats weighing 180–220 g. Experimental modeling of hyperlipidemia – tween model: intraperitoneal administration of tween-80 at a dose of 200 mg/100 g body weight. The test compounds were administered orally, simultaneously with tween, at a dose of 1/10 of LD50 (previously calculated by Prozorovsky express method) for 6 days. The following indicators of lipidogram were determined: total cholesterol (TC), high-density lipoprotein cholesterol (HDL cholesterol), low-density lipoprotein cholesterol (LDL cholesterol), triglycerides (TG) and atherogenic index of plasma: TC – HDL cholesterol / HDL cholesterol. The experiments were carried out with respect to Bioethical rules and norms. Results. The studies have shown data on the hypolipidemic activity of 7-β-hydroxy-γ-aryloxypropylxanthinyl-8-thioalkane acid derivatives. According to the conditional efficiency index Ʃ, which included the overall percentage of the following indicators – total cholesterol, low-density lipoprotein cholesterol and triglycerides, the leading compounds were 2439 (87.47 %), 6047 (82.30 %). The reference drug atorvastatin had a value of 82.98 %. Conclusions. The major compound was 2439 identified among all compared to the control group. The prospect of further research is a more detailed study on the ability of xanthine derivatives to exhibit hypolipidemic effects and to influence oxidative stress in various hyperlipidemic models. Побічні ефекти статинів – нерідке явище, часто визначають диспепсичні розлади, безсоння, головний біль, еритему шкіри, висип. Це спонукає науковців до пошуку нових ефективних і малотоксичних гіполіпідемічних засобів. Різні природні та синтетичні похідні ксантину визнані терапевтично активними сполуками, описані як засоби для боротьби з різними захворюваннями. Тому актуальним є вивчення нових похідних ксантину та їхніх гіполіпідемічних ефектів, які б мали значущий терапевтичний ефект при мінімальній побічній дії. Мета роботи – вивчення впливу похідних 7-β-гідрокси-γ-арилоксипропілксантиніл-8-тіоалканових кислот на показники ліпідограми в експерименті в лабораторних щурів. Матеріали та методи. Об’єкти дослідження – похідні 7-β-гідрокси-γ-арилоксипропілксантиніл-8-тіоалканових кислот. Експерименти виконали на білих лабораторних щурах лінії Вістар масою 180–220 г. Експериментальне моделювання гіперліпідемії – твінова модель: внутрішньоочеревинне введення твін-80 у дозі 200 мг/100 г ваги. Досліджувані речовини вводили перорально одночасно з твіном протягом 6 днів у дозі 1/10 від LD50 (попередньо обрахована за експрес-методом Прозоровського). Визначали показники ліпідограми: рівень загального холестерину (ЗХС), холестерин ліпопротеїдів високої щільності (ХС ЛПВЩ, α-ХС), холестерин ліпопротеїдів низької щільності (ХС ЛПНЩ), тригліцериди (ТГ), холестериновий індекс атерогенності (ХІА) за формулою: ХІА = ЗХС – ХС ЛПВЩ / ХС ЛПВЩ. Під час експерименту дотримувалися біоетичних правил і норм. Результати. У результаті досліджень отримали дані щодо гіполіпідемічної активності похідних 7-β-гідрокси-γ-арилоксипропілксантиніл-8-тіоалканових кислот. За даними експерименту, за показником умовного індексу ефективності Ʃ, який включав суму відсотків таких показників, як загальний холестерин, холестерин ліпопротеїдів низької щільності та тригліцериди, сполуками-лідерами визначено речовини 2439 (87,47 %), 6047 (82,30 %). Препарат-порівняння аторвастатин мав значення 82,98 %. Висновки. Сполука-лідер порівняно з контрольною групою – речовина 2439. Перспективи подальших досліджень передбачають детальніше вивчення похідних ксантину щодо наявності гіполіпідемічної дії та здатності впливати на показники оксидативного стресу на різних моделях гіперліпідемії. Побочные эффекты статинов – нередкое явление, часто отмечают диспепсические расстройства, бессонницу, головную боль, эритему кожи, сыпь. Это мотивирует ученых к поиску новых эффективных и малотоксичных гиполипидемических средств. Различные природные и синтетические производные ксантина признаны терапевтически сильнодействующими соединениями, описаны как средства для борьбы с различными заболеваниями. Поэтому изучение новых производных ксантина и их гиполипидемических эффектов, которые имели бы значительный терапевтический эффект при минимальном побочном действии, является актуальным. Цель работы – изучение влияния производных 7-β-гидрокси-γ-арилоксипропилксантинил-8-тиоалкановых кислот на показатели липидограммы в эксперименте на лабораторных крысах. Материалы и методы. Объекты исследования – производные 7-β-гидрокси-γ-арилоксипропилксантинил-8-тиоалкановых кислот. Эксперименты проведены на белых лабораторных крысах линии Вистар массой 180–220 г. Экспериментальное моделирование гиперлипидемии – твиновая модель: внутрибрюшинное введение твин-80 в дозе 200 мг/100 г веса. Исследуемые вещества вводили внутрь одновременно с твином в течение 6 дней в дозе 1/10 от LD50 (предварительно рассчитана по экспресс-методу Прозоровского). Определяли показатели липидограммы: уровень общего холестерина (ОХС), холестерина липопротеидов высокой плотности (ХС ЛПВП, α-ХС), холестерин липопротеидов низкой плотности (ХС ЛПНП), триглицериды (ТГ) и холестериновый индекс атерогенности (ХИА) по формуле: ХИА = ОХС – ХС ЛПВП / ХС ЛПВП. В ходе эксперимента придерживались биоэтических правил и норм. Результаты. В результате исследований получены данные о гиполипидемической активности производных 7-β-гидрокси-γ-арилоксипропилксантинил-8 тиоалкановых кислот. По данным эксперимента, по показателю условного индекса эффективности Σ, который включал сумму процентов таких показателей, как общий холестерин, холестерин липопротеидов низкой плотности и триглицериды, соединениями-лидерами определены вещества 2439 (87,47 %), 6047 (82,30 %). Препарат-сравнения аторвастатин имел значение 82,98 %. Выводы. Преобладающее по сравнению с контрольной группой соединение – вещество 2439. Перспективы дальнейших исследований предусматривают более глубокое изучение производных ксантина относительно способности проявлять гиполипидемическое действие и влиять на показатели оксидативного стресса на разных моделях гиперлипидемии.
Дослідження впливу похідних 7-β-гідрокси-γ-арилоксипропілксантиніл- 8-тіоалканових кислот на показники ліпідограми в експерименті
Исследование влияния производных 7-β-гидрокси-γ-арилоксипропилксантинил- 8-тиоалкановых кислот на показатели липидограммы в эксперименте
Білай І. М. - ORCID ID: 0000-0002-7574-4093; Романенко М. І. - ORCID ID: 0000-0003-4213-7841; Іванченко Д. Г. - ORCID ID: 0000-0001-9858-2659.
Keywords: xanthines; hyperlipidemia; lipoproteins; ксантини; гіперліпідемія; ліпопротеїди; ксантины; гиперлипидемия; липопротеиды